La gestión por competencias para la evaluación del desempeño laboral. Caso: microempresa (2020)
With the go of time and changes in the global economy, companies adjust their strategies to increase productivity and stay on the economic radar from product-focused variables. This often ignores the human capital of organizations and their internal challenges, translated into the skills, competencies, skills and attitudes of their workers, directing their attention to the customer and setting aside the processes and those who control them.